The relationship between subjective experience of childhood abuse and neglect and depressive symptoms during pregnancy - YOLDEMİR, AHMET TEVFİK; İNANICI, MEHMET AKİF; YILDIZ İNANICI, SİNEM (ELSEVIER SCI LTD, 2017)
Introduction: Childhood abuse and neglect have devastating effects in adulthood such as depression. During pregnancy, depression's effects in women have great importance due to its serious consequences for both children and families. It is aimed to find out a relationship between childhood abuse/neglect and depression among pregnant women. Method: One-hundred-forty-four married and healthy volunteer pregnant women were recruited between February-May 2015 during their regular hospital visit. Beck Depression Inventory and Childhood Trauma Questionnaire were used to evaluate depression and childhood abuse experiences. Results: The participants' mean age was 29.37 years (SD +/- 4.71) and the average duration gestation was 28.81 weeks (SD = 5.05). Depressed women tended to get marry earlier (M = 21.07, SD = 3.47) than the non-depressed group (M = 22.55, SD = 3.36) (p = 0.012) and they had higher number of lifetime gestations (M = 3.31, SD = 2.06) than their non-depressed counterparts (M = 2.33, SD = 1.26) (p = 0.001). Each abuse and neglect score helped to predict the participants' depression scores. Conclusions: Scanning of pregnant women for both depression and childhood trauma will give change to health providers to support this vulnerable group and their prospective children. (C) 2017 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: PSYCHOSOCIAL RISK-FACTORS; OF-THE-LITERATURE; POSTPARTUM DEPRESSION; PERINATAL DEPRESSION; INTERGENERATIONAL TRANSMISSION; POSTNATAL DEPRESSION; SEXUAL-ABUSE; WOMEN; HEALTH; STRESS